Transformation of Values and Character Education in Islamic Education Based on the Qur’an and Hadits - Mukhlis Mukhlis; Husnul Yaqin; Hamdan Hamdan; Hidayat Ma’ruf (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to examine the transformation of values and character education based on the Qur’an and Hadith as a solution to contemporary moral and educational challenges. The research employs a qualitative approach through library research by analyzing various scholarly sources, journal articles, and relevant Islamic educational literature. The findings reveal that values such as gratitude, patience, honesty, justice, compassion, responsibility, and sincerity serve as fundamental principles in shaping students’ character. These values can be effectively internalized through several educational methods, including role modeling, habituation, advice, self-reflection, and storytelling. The study further highlights that the integration of Qur’anic and prophetic values into modern educational practices contributes significantly to the development of students’ spiritual, emotional, and social competencies. The novelty of this research lies in its integrative framework that connects Islamic moral values with transformative character education approaches adaptable to contemporary educational contexts. This study also offers a holistic perspective by emphasizing the practical transformation of Qur’anic and Hadith-based values into sustainable character-building strategies in Islamic education